Central nervous system involvement in patients with HCV-related cryoglobulinemia: review and a case report - D. Filippini; F. Colombo; S. Jann; R. Corneo; B. Canesi (PAGEPress Publications, 2002)
Introduction: Few well-documented cases of central nervous system involvement in patients with mixed cryoglobulinemia and/or HCV infection have been reported. We can distinguish between acute or subacute diffuse and focal lesions (transient ischemic attack-like syndromes and cerebrovascular accidents). Methods: A search of two electronic databases (Medline and EMBASE) was conducted from the year of their inception (1966 for Medline and 1988 for EMBASE) to September 2000. The search strategy employed entailed combining these terms: Cryoglobulinemia, Central Nervous System, Hepatitis C, chronic hepatitis. Cryoglobulinemia and Central Nervous System were also used as free test words. We analysed articles with case reports and the most frequent articles on the references list. Pathogenesis: The main pathophysiologic mechanism of cerebral involvement is ischemia (or rarely hemorrhage) due to diffuse or segmental vasculitis of the small cerebral vessels. In these cases a brain MRI usually shows single or multiple increased T2 signals. Furthermore an occasional occlusive vasculopathy without vasculitis was documented histologically. In these patients ischemia could be started or enhanced by the engorgement of the microvasculature by clumps of red cells and by aggregates of cryoglobulins. In the same patients vasculitis and hemoreological abnormalities can affect the clinical picture of the cerebral involvement in mixed cryoglobulinemia. Finally, the detection of HCV in the lesions induces a hypothesis that, in some cases, CNS involvement could be directly related to chronic HCV infection, even in the absence of cryoglobulin production. Case report: We describe a 63 year-old woman with acute severe encephalopathy. Laboratory evaluation revealed a high positive test result for rheumatoid factor (3390 U/ml) and hypocomplementemia (C4 less than 1.67 mg/dl). Protein immunofixation electrophoresis demonstrated 5% monoclonal proteins (IgM/k and IgG/k), 3% cryoglobulins were present, HCV antibody and HCV-RNA (type 2a-2c) were positive. Cryoglobulins were never typed, because they disappeared after plasma exchanges. Liver enzymes, renal function and findings on cerebrospinal fluid were normal. Cerebral CT and MRI were also normal. Antinuclear antibodies, anti nDNA antibodies, antiphospholipid antibodies, lupus anticoagulant, ANCA, Lyme disease serology, complete tests for thrombophilia were negative. Bone aspiration was normal. The patient, in coma, was treated with two plasma exchanges. During the first treatment she recovered consciousness. Prednisone (1 mg/Kg/day) and cyclophosphamide (400 mg iv for three days) were added. After a week two plasma exchanges were performed again. Liver enzymes and rheumatoid factor were analyzed monthly for six months and than every two months for another six month period up to the present. Liver enzymes were always normal, rheumatoid factor was always at a lower level than the first evaluation (now it's 311 U/ml). At present she is taking Prednisone 5 mg once a day, neurologic syntoms are absent and neurologic examination is normal. Discussion: We can conclude that: central neurologic involvement may be the clinical presentation of HCV infection and mixed cryoglobulinemia. HCV serologic tests and cryoglobulins should be considered in patient with encephalopathy of non-obvious cause; plasma exchange is the treatment of choice in acute severe forms; in some patients HCV could involve directly CNS, even in the absence of cryoglobulin production.